2018
DOI: 10.3389/fimmu.2018.00753
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated CD25 and Cytokine Expression by γδ T Cells of Systemic Sclerosis Patients Stimulated With Cardiolipin and Zoledronate

Abstract: Objectivesγδ T cells, a non-conventional innate lymphocyte subset containing cells that can be activated by lipids and phosphoantigens, are abnormally regulated in systemic sclerosis (SSc). To further evaluate the significance of this dysregulation, we compared how exposure to an autoantigenic lipid, cardiolipin (CL), during co-stimulation with an amino-bisphosphonate (zoledronate, zol), affects the activation and cytokine production of SSc and healthy control (HC) γδ T cells.MethodsExpression of CD25 on Vγ9+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The level of pathogenic CD27 + γδ T cells were reported to increase, with upregulation of granzyme B or perforin expression (134). Further, Vγ9Vδ2, a subset of human γδ T cells, shows anti-fibrotic potential with the production of IFNγ (135,136). An abundance of approximately 8-20% γδ T cells in resident pulmonary lymphocytes shows the possible engagement of γδ T cells in lung infection, chronic inflammation, and subsequent pulmonary fibrosis (137).…”
Section: γδ T Cells and Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…The level of pathogenic CD27 + γδ T cells were reported to increase, with upregulation of granzyme B or perforin expression (134). Further, Vγ9Vδ2, a subset of human γδ T cells, shows anti-fibrotic potential with the production of IFNγ (135,136). An abundance of approximately 8-20% γδ T cells in resident pulmonary lymphocytes shows the possible engagement of γδ T cells in lung infection, chronic inflammation, and subsequent pulmonary fibrosis (137).…”
Section: γδ T Cells and Fibrosismentioning
confidence: 99%
“…Further, it has been reported that skin fibroblasts exhibit higher proliferative activity and stronger collagen synthesis ability when cultured with γδ T cell supernatant ( 133 ). Studies on patients with systemic sclerosis have demonstrated the involvement of γδ T cells ( 134 136 ). The level of pathogenic CD27 + γδ T cells were reported to increase, with upregulation of granzyme B or perforin expression ( 134 ).…”
Section: The Role and Mechanisms Of T Cells In Fibrosis And Fibrotic mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a subset of Gamma-delta T cells (Tγδ) increased in Multiple Sclerosis (MS) patients has been shown to be activated by cardiolipin. Although their exact role is still not clear, it suggests an important role for cardiolipin also activating adaptive immune responses during CNS disease progression ( 81 ).…”
Section: Mitochondrial Damps and Neurodegenerationmentioning
confidence: 99%
“…CL also decreased IFNγ secretion of SSc Vδ1 + T cells relative to HC. Thus, CD1d mediated interactions of Vδ1 + T cells in SSc may play a profibrotic role via effects on pro and anti fibrotic cytokines, in particular in the context of simultaneous Vγ9 + T cell triggering [109].…”
Section: Functions and Subsets Of γδ T Cells In Sscmentioning
confidence: 99%